Toward Intelligent and Secure 5G-IIoT Networks: A Framework for AI-Driven Optimization and Blockchain-Based Security - Joe Laksamana Silitonga (International Journal of Information System and Innovative Technology, 2025)
The rapid evolution of 5G networks has unlocked new capabilities for the Industrial Internet of Things (IIoT), enabling ultra-reliable, low-latency, and scalable communication. However, challenges such as dynamic resource allocation, network congestion, and growing cybersecurity threats continue to limit the full potential of 5G-IIoT integration. Building upon previous literature, this paper proposes a novel architectural framework that combines artificial intelligence (AI) for intelligent network optimization and blockchain technology for decentralized, secure data management.The framework introduces a layered system comprising four integrated components: AI-driven resource management, a permissioned blockchain layer for secure authentication, an edge-cloud coordination module for low-latency computing, and a network slicing orchestrator for application-specific service differentiation. Each component is designed to address specific limitations in existing 5G-IIoT deployments by enhancing adaptability, reducing security risks, and optimizing performance.This paper outlines the architectural design, data flow, and interaction between components. It also defines the evaluation metrics and simulation setup for benchmarking the proposed framework against conventional 5G-IIoT systems. Preliminary findings and existing literature suggest that integrating AI and blockchain mechanisms can significantly improve latency, throughput, energy efficiency, and security resilience.This work aims to serve as a foundational blueprint for building intelligent, secure, and future-ready IIoT infrastructures powered by 5G. Future work will focus on simulation, real-world deployment, and integration with upcoming 6G paradigms.